Diagnostic Value of Nuclear Hybrid Imaging in Malignant Struma Ovarii: A Systematic Review of Case Reports - Claudiu Peștean; Doina Piciu (Diagnostics)
Background: Struma ovarii is a rare tumor, a type of ovarian mature teratoma consisting over 50% of its mass in thyroid ectopic tissue; 5% to 10% of cases, as described in the literature, are malignant and well known as malignant struma ovarii or thyroid cancer from struma ovarii. Due to the limited number of malignant struma ovarii cases, the diagnostic and therapeutic approach of malignant struma ovarii lacks in standardization. Methods: We performed a comprehensive search on the English language PubMed and Google Scholar. We used specific controlled keywords “PET CT”, “SPECT CT”, “PET MRI”, “malignant struma ovarii”, “hybrid imaging” and “mature ovarian teratoma”. Upon the retrieval of potential articles, we analyzed them for their eligibility. The inclusion criteria were: articles discussing the role of PET/CT and SPECT/CT hybrid imaging in malignant struma ovarii, full-text articles on the topic of interest and English publications. The exclusion criteria were articles not directly related to the hybrid imaging and not discussing the subject of malignant struma ovarii. Results: A total of 64 articles were screened, 35 duplicates were eliminated, 15 articles excluded and a total number of 14 articles were included for this systematic review, 13 of them being case reports and one being a case report with a systematic review. F-18 FDG PET/CT contributed in seven cases (50%), I-131 NaI SPECT/CT in seven cases (50%) and I-124 NaI PET/CT in two cases (14.29%). In two cases, 131 NaI SPECT/CT and F-18 FDG PET/CT were used as complementary investigation tools. The hybrid imaging methods used as a part of the diagnostic strategy were accompanied by several diagnostic alternatives: ultrasounds, CT, MRI, I-131 NaI WBS and I-123 NaI WBS. Conclusions: There is no consistent or standardized diagnostic and therapeutic approach for malignant struma ovarii. Hybrid imaging methods may be of great value in initial diagnostic and the association of F-18 FDG PET/CT and I-131 NaI SPECT/CT is a successful diagnostic approach. The association of hybrid imaging with other diagnostic imaging alternatives in initial diagnostic and follow up is essential.